Simulation and Optimization for Interior Sound Field of a Rail Vehicle. (July 2014) - Hu, K.; Wang, Y.S.; Guo, H.; Chen, H.
A simulation and optimization scheme for reducing interior noise of rail vehicles is investigated in this paper. A sample subway of Shanghai Metro Line 9 is considered. Firstly, some interior noises are measured when the subway is running at a speed of 60 km/h. The A-weighted sound pressure levels (SPLs) of the measured noise signals are analyzed. A finite element model of the subway carriage is established based on its structural parameters, and then the Actran software is selected and used for acoustical simulation. The accuracy of the finite model is verified by comparing the one-third-octave SPL values from the simulations and measurements. According to the simulated sound field, several positions with relatively high SPLs in the carriage are determined for interior noise improvement. By using orthogonal experimental design, finally, the best noise reduction scheme is put forward, which obtained an optimized SPL reduction of 4.81dB. The proposed scheme may be extended to other rail vehicles for improving interior acoustic environment.